Selective inhibition of carboxypeptidase U may reduce microvascular thrombosis in rat experimental stroke. (1st October 2020) - Mertens, Joachim C.; Boisseau, William; Leenaerts, Dorien; Di Meglio, Lucas; Loyau, Stéphane; Lambeir, Anne‐Marie; Ducroux, Célina; Jandrot‐Perrus, Martine; Michel, Jean‐Baptiste; Mazighi, Mikael; Hendriks, Dirk; Desilles, Jean‐Philippe
Abstract: Background: Carboxypeptidase U (CPU, CPB2, TAFIa) is a potent attenuator of fibrinolysis. The inhibition of CPU is thus an interesting strategy for improving thrombolysis. Objectives: The time course of CPU generation and proCPU consumption were assessed in an experimental rat model of acute ischemic stroke (AIS). In addition, the effects of the selective CPU inhibitor AZD9684 on CPU kinetics, microvascular thrombosis (MT), and AIS outcome were evaluated. Methods: Rats were subjected to transient middle cerebral artery occlusion (tMCAO) and received recombinant tissue‐type plasminogen activator (tPA), a specific CPU inhibitor (AZD9684), combination therapy of tPA and AZD9684, or saline for 1 hour using a randomized treatment regime. CPU and proCPU levels were determined at five time points and assessed in light of outcome parameters (a.o.: infarct volume and fibrin[ogen] deposition as a measure for MT). Results: Clear activation of the CPU system was observed after AIS induction, in both saline‐ and tPA‐treated rats. Maximal CPU activities were observed at treatment cessation and were higher in tPA‐treated animals compared to the saline group. Concomitant proCPU consumption was more pronounced in tPA‐treated rats. AZD9684 suppressed the CPU activity and reduced fibrin(ogen) deposition, suggesting a reduction of MT. Nonetheless, a significant decrease in infarct volume was not observed. Conclusions: A pronounced activation of the CPU system was observed during tMCAO in rats. Selective inhibition of CPU with AZD9684 was able to reduce fibrin(ogen) deposition and brain edema, suggesting a reduction of MT but without a significant effect on final infarct volume.